Growing fast food consumption and obesity in Asia: Challenges and implications. (January 2021) - Wu, Yang; Wang, Liang; Zhu, Jiang; Gao, Liwang; Wang, Youfa
Abstract: It is widely believed that better access to fast food (FF) outlets increases FF consumption and thus the risk of obesity; yet, thus far, there are limited results to support this conclusion in Asian countries. A recent study by Hall and his colleagues (in press) examined the cross-sectional relationship between FF restaurant density and the likelihood of being overweight or obese among 1388 female Filipino migrant workers living in Macao, China. It found that FF restaurant density within a 0.5-mile buffer zone around one's home was significantly associated with a 7% increase (95% CI: 1%–14%) in the odds of being overweight or obese in this population. Based on these findings, the authors suggested improving access to healthy foods as one of the means to fight the obesity epidemic. The current article examines literature 1) on the relationship between obesity, FF consumption, and access to FF outlets; 2) on different measures of access to FF outlets; 3) on potential confounders and effect modifiers such as neighborhood deprivation and transportation; and 4) on challenges and implications for researchers and policymakers. Considering the growing consumption of FF and obesity rates in many countries especially in developing countries, it is important to regulate the FF industry and help consumers improve their related knowledge and behaviors. We also recommend that government policies abate obesogenic environments and thus curb the obesity epidemic in the future. Highlights: Findings about association between fast food outlet density and obesity inconclusive. Measuring access to fast food outlets is a complex issue. More studies are needed to understand "food deserts" in Asia countries. The influence of food environments on obesity deserves further study in immigrants.